Measuring the Energy of Economics (E): The Case of China - Estrada, Mario Arturo Ruiz (WILAYAH: The International Journal of East Asian Studies, 2014)
This paper proposes the application of the special theory of relativity by Professor Albert Einstein in economics. It is based on the measurement of the energy of the economics (E). The construction of the energy of the economics (E) request the uses two economic variables into the specific theory of relativity follow by: The unemployment growth rate and the technological development speed. Finally, the energy of the economics (E) has been applied for the case of China.